Fundamental studies of high-aspect ratio UV embossing of poly(ethylene glycol) - Neo, Wee Koon (2008)
Two critical aspects determining if the embossed polymer could be demolded cleanly are the mold-resin chemical interaction, and the conversion and shrinkage upon curing. This thesis examines the fundamentals of these physical processes using PEG as the base material.